Correction to: Decisional Balance Inventory (DBI) Adolescent Form for Smoking: Psychometric Properties of the Persian Version - Maryam Khazaee-Pool; Tahereh Pashaei; Koen Ponnet; Fatemeh Jafari; Rashin Alizadeh (BMC Public Health, 2017)
Correction After publication of the article [1], it has been brought to our attention that the first and last names of the third author were transposed in the original article. The author was published as “Ponnet Koen” where in fact the correct name is “Koen Ponnet”. The original article has been revised to reflect this.